STATE SUPPORT FOR RESEARCH IN PHARMACOLOGY: AN ANALYSIS OF FOREIGN AND DOMESTIC EXPERIENCE - Alexey Semin (Belgorod National Research University, 2017)
Introduction: The goal of research was to analyze the management of innovative activities for innovative medicines market launch in Russia and abroad. Materials and methods: In the study there were used methods of cognition, including methods of empirical (observation, comparison) and theoretical studies (analysis, synthesis, aggregation), scientific assessment, SWOT-analysis. Results and discussion: The analysis of domestic and foreign experience in the planning and management of research in pharmacology was carried out. Despite the fact that at the present time in the Russian Federation a powerful ramified state apparatus for regulating scientific research and development in the field of medicine has been formed, the pharmacological science remains divided. This leads to a reduction of efficiency of innovative drugs development studies. At the same time, in developed countries, interdepartmental coordination and advisory bodies (councils, commissions) are active, often at the highest level. This testifies to the high attention given in these countries to interdepartmental interaction and intersectoral projects in the field of research and development. Conclusion: Foreign R & D support systems are characterized by a number of differences from domestic mechanisms. A number of recommendations based on the experience of foreign colleagues for future measures to modernize existing and introduce new mechanisms for state support of research in the field of pharmacology in Russia were proposed.